Autophagy plays a protective role in Mn-induced toxicity in PC12 cells. (1st February 2018) - Zhou, Qian; Fu, Xiaolong; Wang, Xueting; Wu, Qin; Lu, Yuanfu; Shi, Jingshan; Klaunig, James E.; Zhou, Shaoyu
Abstract: Excessive environmental or occupational exposure to manganese (Mn) is associated with increased risk of neuron degenerative disorders. Oxidative stress and mitochondrial dysfunction are the main mechanisms of Mn mediated neurotoxicity. Selective removal of damaged mitochondria by autophagy has been proposed as a protective mechanism against neuronal toxicant-induced neurotoxicity. Whether autophagic flux plays a role in Mn-induced cytotoxicity remains to be fully elucidated. The present study was designed to investigate the effect of Mn exposure on autophagy, and how modulation of autophagic flux alters the sensitivities of cells to Mn-elicited cytotoxicity. Rat adrenal pheochromocytoma PC12 cells were treated with Mn for 24 h to establish a cellular mode of Mn toxicity. Treatment of cells with Mn resulted in increased expression of autophagic marker LC3-II protein, as well as accumulation of p62, indicating an interference of autophagy flux caused by Mn. Pre-incubation of cells with antioxidant N-acetyl-l -cysteine (NAC) or resveratrol improved cell survival, accompanied by decreased LC3-II expression and increased expression level of p62, suggesting a down regulation of autophagy flux. To further determine the role of autophagy in Mn-induced cytotoxicity, the effect of chloroquine and rapamycin on cell viability was examined. Inhibition of autophagy flux by chloroquine exacerbated Mn-induced cytotoxicity, while induction of autophagy by rapamycin significantly reduced cell death caused by Mn. Furthermore, it was found that rapamycin, NAC and resveratrol improved cellular oxygen consumption accompanied by a decrease in cellular ROS generation and increase in GSH level, while chloroquine suppressed cellular respiration and deteriorated cellular oxidative stress. Collectively, these results demonstrate that autophagy plays a protective role in Mn-induced cell toxicity. Antioxidants NAC and resveratrol confer protective role in Mn toxicity mainly through maintaining mitochondrial dynamics and function, other than a modulation of autophagy flux.